Analisis Kredit Bermasalah Pada PT. Bank Perkreditan Rakyat Asparaga Adiguna Bersama Provinsi Gorontalo - Bakri Bakri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
The aims of this study is to describe the cause of the non-performing loans on the PT. BPR Asparaga Adiguna Bersama and to describe policy in rescue and settlement of non-performing loans.The method used in this research is qualitative research with a descriptive approach. Collected data is a primary and secondary data by employing interview techniques and documentation.The result of the study showed that (1) non performing loan to four accasioned factor, that is: the lack of officers accuracy in loan analysis, the bad faith of officers of PT BPR Asparaga Adiguna Bersama, the lack of loan suvervision system, and economic downturn. (2) the effort which wasdone to overcome the non performing loan at PT. BPR Asparaga Adiguna Bersama wererestructuring, rescheduling, foreclosure bail, and write off (account receivable deletion).